2015
DOI: 10.1080/07399332.2014.992521
|View full text |Cite
|
Sign up to set email alerts
|

Female Genital Mutilation (FGM): Australian Midwives’ Knowledge and Attitudes

Abstract: Female genital mutilation (FGM) is a women's health and human rights issue attracting global interest. My purpose in this qualitative study was to report the knowledge and attitudes of Australian midwives toward FGM. Verbatim transcription and thematic analysis of semistructured interviews with 11 midwives resulted in these themes: knowledge of female genital mutilation and attitude toward female genital mutilation. Significant gaps in knowledge about FGM featured prominently. The midwives expressed anger towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 23 publications
5
35
0
Order By: Relevance
“…In fact, the quality assessment of included studies revealed that only one study had a high methodological quality [35]. Ten (10) studies had moderate methodological limitations [3645], two were rated as being of low quality [46, 47], and the scientific report of one study provided very limited information for the reader to assess the rigor and quality of the research and was therefore judged as being of very low quality [48]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, the quality assessment of included studies revealed that only one study had a high methodological quality [35]. Ten (10) studies had moderate methodological limitations [3645], two were rated as being of low quality [46, 47], and the scientific report of one study provided very limited information for the reader to assess the rigor and quality of the research and was therefore judged as being of very low quality [48]. …”
Section: Resultsmentioning
confidence: 99%
“…Some studies mentioned the legal liability of health-care providers as a reason for not performing FGM [36, 4446]. This was mainly found in countries where FGM is not the norm (Belgium, Australia and United-States of America).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations